Multistep Photoluminescence Decay Reveals Dissociation of Geminate Charge Pairs in Organolead Trihalide Perovskites. Issue 17 (11th May 2017) - Augulis, Ramūnas; Franckevičius, Marius; Abramavičius, Vytautas; Abramavičius, Darius; Zakeeruddin, Shaik Mohammed; Grätzel, Michael; Gulbinas, Vidmantas
Abstract : Charge carrier dynamics in organolead iodide perovskites is analyzed by employing time‐resolved photoluminescence spectroscopy with several ps time resolution. The measurements performed by varying photoexcitation intensity over five orders of magnitude enable separation of photoluminescence components related to geminate and nongeminate charge carrier recombination and to address the dynamics of an isolated geminate electron–hole pair. Geminate recombination dominates at low excitation fluence and determines the initial photoluminescence decay. This decay component is remarkably independent of the material structure and experimental conditions. It is demonstrated that dependences of the geminate and nongeminate radiative recombination components on excitation intensity, repetition rate, and temperature, are hardly compatible with carrier trapping and exciton dissociation models. On the basis of semiclassical and quantum mechanical numerical calculation results, it is argued that the fast photoluminescence decay originates from gradual spatial separation of photogenerated weakly bound geminate charge pairs. Abstract : Ultrafast time‐resolved measurements of methylammonium lead halide perovskite photoluminescence enable separation of the fast and slow decay components attributed to the geminate and nongeminate charge carrier recombination. The geminate recombination dominates at very low excitation intensities during initial several tens of picoseconds and reveals the gradual spatial separation of photogenerated weakly bound geminate charge pairs.